Network Monitoring Using Zabbix ICMP Ping and Telegram Notifications Using the Network Development Life Cycle Model - Febriana; Retno Waluyo; Dinar Mustofa (Universitas Dinamika, 2026)
This study addresses the critical need for proactive network management in MSMEs, where reliance on stable connectivity is high but existing monitoring tools are often costly or reactive. We propose a low-cost, proactive monitoring framework that integrates the open-source Zabbix platform with ICMP Ping detection and real-time Telegram Bot notifications. Developed using the Network Development Life Cycle (NDLC) methodology, the system’s novelty lies in its practical integration of instant messaging to achieve near real-time fault notification in a scalable environment. Implemented at an ISP (CV Media Computindo) managing over 250 active clients, the framework was evaluated using 61 client devices on a virtualized Ubuntu Server. Experimental results demonstrate high operational impact: failure notifications were delivered in under two seconds with a 100% success rate, significantly reducing average device downtime from 30 minutes to just 3 minutes. Despite minor limitations regarding polling intervals and external messaging dependencies, the system proved highly effective and cost-efficient. This research provides a scalable foundation for resource-constrained organizations to enhance network reliability through open-source tools and offers a benchmark for future comparative studies with enterprise platforms like PRTG, Nagios, and Prometheus.